2022
DOI: 10.30541/v42i4iipp.941-960
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Economic Reforms and Trade Liberalisation on Agricultural Export Performance in Pakistan

Abstract: Economic reforms and trade liberalisation policies have been widely adopted in developing countries in recent years. Pakistan is no exception. This paper focuses on the effects of economic reform policies on the agricultural export performance. A number of studies have investigated the effects of trade liberalisation on export growth in developing countries, and have reached inconclusive results. Some studies have identified positive effects of trade liberalisation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…The share of agricultural exports in overall Pakistan exports was 20% in 2014-15 and that was nineteen percent in 2013-14 (source: Economic survey). The empirical result of agricultural-exports is consistent with the studies of (Bashir, 2003;Nadeem, 2007;Anwar, 2010;Mahmood, 2010;and Malik, 2010). The results further reveal that agricultural-imports are positive and highly significant indicating that it may lead to an affirmative change of about 0.57% is consistent with the study of Sharif et al (2010) and Faridi (2012).…”
Section: Co-integration and Bounds Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…The share of agricultural exports in overall Pakistan exports was 20% in 2014-15 and that was nineteen percent in 2013-14 (source: Economic survey). The empirical result of agricultural-exports is consistent with the studies of (Bashir, 2003;Nadeem, 2007;Anwar, 2010;Mahmood, 2010;and Malik, 2010). The results further reveal that agricultural-imports are positive and highly significant indicating that it may lead to an affirmative change of about 0.57% is consistent with the study of Sharif et al (2010) and Faridi (2012).…”
Section: Co-integration and Bounds Analysissupporting
confidence: 86%
“…In 1990s, the increase in annual average export was 5.6% whereas imports increased by 3.2% shaping an average trade deficit of -0.6%. The share of agricultural goods was declining and recorded as nineteen percent of total exports which reduced further to twelve percent in 1999-2000 (Bashir, 2003). Likewise, the share of manufactured goods in overall exports rose to seventy-three percent in 1999-2000 from fifty-seven percent in 1990-91.…”
Section: Introductionmentioning
confidence: 98%
“…In line, Verter and Bečvářová ( 2016 ) examined the linkage between agricultural export and output growth for the period 1980–2012 by employing ordinary least squares (OLS) for Nigeria. The findings revealed that agricultural export enhances output growth while these result in the same line for instance (Abbas 2012 ; Quddus and Saeed 2005 ; Haleem et al 2005 ; Bashir and Din 2003 ; Shahbaz et al 2015 ) for Pakistan.…”
Section: Literature Reviewmentioning
confidence: 71%
“…Hudson and Ethridge (1998) estimated that Pakistan's cotton export has fallen by 58 per cent from 1988 to 1995, because of imposition of tax on export of cotton lint. According to Bashir (2003), Pakistan's agriculture export performance is enormously receptive to internal economic policies and trade reforms. Pakistan is expected to continue its competiveness in the free/preferential trading environment through quality production and marketing mechanism along with reduction in cost.…”
Section: Review Of Previous Literaturementioning
confidence: 99%